PENGARUH KARAKTERISTIK PEKERJA TERHADAP KEJADIAN MUSCULOSKELETAL DISORDER PADA PEKERJA PABRIK TENUN MASARI PEMALANG - Pandu Reviami Sandi; Ekawati Ekawati; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Musculoskeletal disorder ( msds ) was a term used which are aimed at a disorder in a muscle that happened in the muscles of order that was felt to be someone starting from complaints mild to the complaints that are heavy. One cause its work tools that are not ergonomic may cause an impact such as the occurrence of musculoskeletal disorder. The purpose of this research was to determine the individual factors (age, body mass index, smoking habit) and occupational factors (tenure, repetitive movements, work sitting position) that influenced to the occurrence of musculoskeletal disorder on worker of MASARI weave factory in Pemalang. The method of this research used survey research approach with cross sectional study design Total sampling taken in this research is 33 workers. Statistical test data of rank spearman correlation performed indicated that there was no correlation between (body mass index, smoking habit, work sitting position) and there was a correlation between working period and the occurrence of musculoskeletal disorder (P-value = 0.03). There was a correlation between age and the occurrence if musculoskeletal disorder (p-value = 0.001). Based on statistical test of multiple regressions, there were variables that had influence toward the occurrence of musculoskeletal disorder; the variables were working period and age. In conclusion, age was more influential to musculoskeletal than working period (working period t=3.564, age t=6.119). the new recruitment workers better age >35 tahun and working period >35 tahun.